Studying of S- and L- form Brucella’s Thermo-Extracts Immunogenic Characteristics at Cavies Guinea Pigs - L. M. Mikhailov; N. L. Barannikova; L. E. Tokareva; S. A. Vityazeva; T. P. Starovoytova; V. I. Dubrovina; S. V. Balakhonov (Эпидемиология и вакцинопрофилактика, 2016)
Relevance. In the Russian Federation is noted the negative dynamics of epizootic process of brucellosis among epidemiologically important species of farm animals (cattle and small ruminants), which represents a threat to the population. Used in Russia live vaccine based on a strain of Brucella abortus 19 the BA has reduced virulence, but capable at high doses (108 -2 109 m.c.) cause a generalized infection in guinea pigs and humans, and in violation of the rules cause post-vaccination complications. Goal. Assess possibility of the thermo-extract derived from the S- and L-forms of Brucella, get an immune response in guinea pigs, and reduce the risk of infection with virulent brucella. Materials and methods. Two series of experiments were carried out on guinea pigs. Immunized guinea pigs thermo-extracts (TE) from a strain of B. abortus I-206 in the S- and L-forms, and live brucellosis vaccine (Scientific and Production Association for Immunological Preparations «Microgen», Russia). To infect guinea pigs using virulent B. abortus 544 (Reference) and B. melitensis I-203 from the museum of living cultures of the Irkutsk Scientific Research Anti-Plague Institute. Results. In the first and second experiment after immunization L TE in dose 5 mg and 10 mg after infection with B. abortus and B. melitensis 5441-203 were approximately similar results. Immunization of Brucella in TE S-form or complex of L + S TE either of two doses (5 mg or 10 mg) cultures after infection B. abortus and B. melitensis 5441-203 gave the same result as a vaccine B. abortus 19VA. Conclusions. The results indicate the prospects of further study of experimental steps for using immunizing agents TE S, L TE and TE S + L on the laboratory animals.